2003
DOI: 10.1085/jgp.200308813
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Single Voltage-gated Proton Channels in Human Eosinophils Estimated by Noise Analysis and by Direct Measurement

Abstract: Voltage-gated proton channels were studied under voltage clamp in excised, inside-out patches of human eosinophils, at various pHi with pHo 7.5 or 6.5 pipette solutions. H+ current fluctuations were observed consistently when the membrane was depolarized to voltages that activated H+ current. At pHi ≤ 5.5 the variance increased nonmonotonically with depolarization to a maximum near the midpoint of the H+ conductance-voltage relationship, g H-V, and then decreased, supporting the idea that the noise is generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
123
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(131 citation statements)
references
References 35 publications
5
123
1
2
Order By: Relevance
“…The human proton channel hH V 1, has an estimated conductance of 78 fS at physiological pH and human body temperature [111]. Given a large driving force, say 100 mV, one channel would carry 7.8 fA of H þ current, which translates into 5 Â 10 4 H þ s 21 .…”
Section: A Digression On Why Proton Channels Carry Such Tiny Currentsmentioning
confidence: 99%
“…The human proton channel hH V 1, has an estimated conductance of 78 fS at physiological pH and human body temperature [111]. Given a large driving force, say 100 mV, one channel would carry 7.8 fA of H þ current, which translates into 5 Â 10 4 H þ s 21 .…”
Section: A Digression On Why Proton Channels Carry Such Tiny Currentsmentioning
confidence: 99%
“…Under optimal conditions, seals can reach the TΩ (10 12 Ω) range (37). This high resistance seal allows recordings with very little background noise and small leak currents (i.e., current that flows from the pipette into the bath through the seal, rather than through the membrane).…”
Section: Seal Formationmentioning
confidence: 99%
“…Recording small currents with the patch clamp technique requires a large signal-to-noise ratio. The smallest directly-recorded single-channel currents were ~8 fA proton channel currents in human eosinophils (37). Noise in the patch clamp set-up arises from the electronic circuitry, the pipette and holder assembly, the seal and cell membrane, and extraneous mechanical or electrical sources (36,75).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimates of the rate of free proton generation indicate that catastrophic acidification would occur within the cell unless an efficient proton extruding mechanism was activated in parallel with electron transport (Rotstein et al, 1987). Several studies have shown that a voltage-dependent, Zn 2+ -sensitive plasma membrane proton channel is activated in parallel with the increase in NADPH oxidase activity Cherny et al, 2003;DeCoursey et al, 2001;DeCoursey et al, 2003;Gordienko et al, 1996;Petheo et al, 2003). This channel is regulated by mediators that increase PKCδ activity and, following PKC activation, the cytosolic pH (pH i ) does not significantly change in response to increases in superoxide production (Bankers-Fulbright et al, 2001).…”
Section: Introductionmentioning
confidence: 99%